2016
DOI: 10.1159/000445548
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis B Infection is Associated with Decreased Risk of Preeclampsia: A Meta-Analysis of Observational Studies

Abstract: Background/Aims: Preeclampsia is a complex multi-system obstetric syndrome and remains one of the leading causes contributing to maternal and perinatal mortality and morbidity. Previous epidemiological studies regarding the association between chronic hepatitis B virus (CHB) infection and the risk of preeclampsia have reported inconsistent results. Therefore, we conducted a meta-analysis to investigate the association between CHB infection and preeclampsia. Methods: The electronic database was searched until J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Of these studies, only one reported calibration statistics for the described model 90 and one found that, of the 14 primary model development studies assessed, only six reported model calibration 78 . The remaining prediction-modeling papers 133 1/1 Low Blood pressure 57, 61 2/2 High Maternal infection (any) 62, 123 2/2 Low Hepatitis B 81 1/1 (neg) Moderate HIV 50,51,62,123 0/4 Very low Periodontal disease 62,82,85,128,142 5/5 Low Mental stress 37 1/1 Low Intrauterine device use 99 1/1 (neg) Low Physical activity levels 122 1/1 (neg) Low Polycystic ovary syndrome 33,119 2/2 Low Blood group A or AB 73, 100 2/2 Moderate Celiac disease 135 0/1 Low Cigarette smoker 141 1/1 (neg) Moderate Dietary factors 127 1/1 Very low Flow-mediated dilatation 143 1/1 Low Interpregnancy interval 64,87 0/2 Moderate Sleep-disordered breathing 29,66 2/2 Moderate Antiphospholipid syndrome 69,133 2/2 Moderate Chronic hypertension 133 1/1 Moderate Pre-existing diabetes 69,133 2/2 Moderate Previous FGR 133 0/1 Low Systemic lupus erythematosus 133 1/1 Low Chronic kidney disease 133 1/1 Low Previous abruption 133 1/1 Low Previous pre-eclampsia 69 61,…”
Section: Multivariable Prediction Modelsmentioning
confidence: 99%
“…Of these studies, only one reported calibration statistics for the described model 90 and one found that, of the 14 primary model development studies assessed, only six reported model calibration 78 . The remaining prediction-modeling papers 133 1/1 Low Blood pressure 57, 61 2/2 High Maternal infection (any) 62, 123 2/2 Low Hepatitis B 81 1/1 (neg) Moderate HIV 50,51,62,123 0/4 Very low Periodontal disease 62,82,85,128,142 5/5 Low Mental stress 37 1/1 Low Intrauterine device use 99 1/1 (neg) Low Physical activity levels 122 1/1 (neg) Low Polycystic ovary syndrome 33,119 2/2 Low Blood group A or AB 73, 100 2/2 Moderate Celiac disease 135 0/1 Low Cigarette smoker 141 1/1 (neg) Moderate Dietary factors 127 1/1 Very low Flow-mediated dilatation 143 1/1 Low Interpregnancy interval 64,87 0/2 Moderate Sleep-disordered breathing 29,66 2/2 Moderate Antiphospholipid syndrome 69,133 2/2 Moderate Chronic hypertension 133 1/1 Moderate Pre-existing diabetes 69,133 2/2 Moderate Previous FGR 133 0/1 Low Systemic lupus erythematosus 133 1/1 Low Chronic kidney disease 133 1/1 Low Previous abruption 133 1/1 Low Previous pre-eclampsia 69 61,…”
Section: Multivariable Prediction Modelsmentioning
confidence: 99%
“…Although the clinical symptoms of patients with PE present after 20 weeks of gestation, the molecular events leading to its onset have been suggested to occur early in pregnancy. As many studies on the mechanism of PE are focused on polymorphisms or chronic hepatitis B infection, RNAs (circRNAs) are rapidly gaining prominence recently [4-7]. …”
Section: Introductionmentioning
confidence: 99%
“…The hepatitis B carrier status is negatively associated with pre-eclampsia 27 . In a meta-analysis of 11 566 Asian patients, chronic hepatitis B infection is associated with 23% decreased risk of pre-eclampsia and increased risks of gestational diabetes 28 . This is compatible with our finding of hepatitis B carrier status being a protective factor for FGR as pre-eclampsia is a risk factor for FGR.…”
Section: Discussionmentioning
confidence: 99%